2015
DOI: 10.1097/hjh.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular dilatation and subclinical renal damage in primary hypertension

Abstract: Left ventricular dilatation is associated with subclinical renal damage in hypertension. These findings extend previous reports and provide a pathophysiological rationale for the observed unfavourable prognosis in patients with left ventricular dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In the present study, a positive correlation was found between LV dilatation, functions, and RRI. Ratto et al [26] also reported a correlation between LV dilatation, functions, and RRI. LV hypertrophy (eccentric and concentric hypertrophy) has been established to be an independent predictor of RRI in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, a positive correlation was found between LV dilatation, functions, and RRI. Ratto et al [26] also reported a correlation between LV dilatation, functions, and RRI. LV hypertrophy (eccentric and concentric hypertrophy) has been established to be an independent predictor of RRI in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Dilated LV geometries as identified by this new classification have been shown to be strongly related to the presence of microalbuminuria in a large group of hypertensive patients. 21 Furthermore, when this classification was applied to high-risk hypertensive patients enrolled in the LIFE trial, it revealed significant differences in haemodynamic patterns and LV function 22 and enhanced prediction of cardiovascular prognosis. 10 In fact, both dilated and Metabolic syndrome and left ventricular dilatation E Ratto et al concentric patterns were found to be associated with increased incidence of cardiovascular events, whereas the eccentric nondilated group was not.…”
Section: Discussionmentioning
confidence: 99%
“…31 More interestingly, in the multivariate analysis arterial stiffness was an independent determinant of increased RRI, suggesting an independent association between renal hemodynamics and arterial stiffness. 33 This ratio of ultrasound determined renal volume to intra parenchymal resistive index has been proposed as a measure of nephroangiosclerosis and has been shown to be useful in identifying patients characterized by reduced kidney volume and increased renovascular stiffness. According to another recent study in 171 unselected subjects, RRI was significantly and independently associated with central pulse pressure and left ventricular systolic and diastolic Doppler blood flow indexes.…”
Section: Rri and Targ E T Org An Damag E In E Ss Ential Htnmentioning
confidence: 99%
“…32 In the same lines, in a total of 449 untreated hypertensives, left ventricular dilatation has been associated with subclinical renal damage, namely albuminuria and early intrarenal vascular changes, expressed as the renal volume to RRI ratio. 33 This ratio of ultrasound determined renal volume to intra parenchymal resistive index has been proposed as a measure of nephroangiosclerosis and has been shown to be useful in identifying patients characterized by reduced kidney volume and increased renovascular stiffness. 33…”
Section: Rri and Targ E T Org An Damag E In E Ss Ential Htnmentioning
confidence: 99%